“AHMAD YASSAVIY” ROMANIDA IBORA VA MAQOLLARNING QO‘LLANILISHI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the features of the use of phraseological units and proverbs in the novel “Ahmad Yassaviy” by Sa’dulla Siyoyev. The study highlights the role of stable expressions, proverbs, and wise sayings characteristic of folk oral tradition in the artistic language of the work. It also explains, through examples, the function of phraseological units and proverbs in revealing the characters’ traits, figuratively depicting events, and strengthening the artistic and aesthetic impact of the work.